Phenotypic variation of Wittrockia cyathiformis (Bromeliaceae) across life forms and forest types in the Atlantic Rainforest - Kamila Grzebielucka; Felipe Micali Nuvoloni; Rosângela Capuano Tardivo (Plant Ecology and Evolution)
Background and aims – This study investigates the phenotypic plasticity of Wittrockia cyathiformis (Bromeliaceae), an endemic species of the Atlantic Rainforest, with the aim of evaluating its morphological variation in relation to different life forms and forest types, specifically Dense Ombrophilous Forest and Mixed Ombrophilous Forest. Material and methods – Field collections were conducted in State Conservation Units and Campos Gerais National Park in Paraná during 2022 and 2023. We measured vegetative morphometric parameters of six to eight bromeliads for each life form (epiphytic, saxicolous, and terrestrial) in each forest type, totalling 43 specimens, with 22 from Dense Ombrophilous Forest and 21 from Mixed Ombrophilous Forest. Additionally, we assessed the national conservation status of the species in Brazil. Key results – The different forest types of the Atlantic Forest exert a greater influence on the phenotypic variation of W. cyathiformis than life forms, with only leaf sheath length being greater in epiphytes and smaller in terrestrials. On the other hand, significant variations in leaf morphometry, such as leaf width and spine size, were strongly associated with the bioclimatic conditions of each forest type. Specimens from Dense Ombrophilous Forest exhibit characteristics typical of species adapted to warm and humid environments, with broader leaves, whereas those from Mixed Ombrophilous Forest have narrower leaves and smaller spines. Conclusion – The different life forms of this species do not result in significant morphometric changes. However, its phenotypic plasticity is strongly influenced by the different forest types, which may favour adaptation to variable environmental conditions. Despite this adaptive capacity, W. cyathiformis is classified as endangered (EN) in its area of occupancy in Brazil. The ongoing habitat loss highlights the need for conservation measures to ensure the long-term persistence of its populations.